(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Comparison of various languages of the world shows us that word order may be mainly of two types: a fixed word order, as for instance, in the English and German languages, where the slightest deviation form the norm is considered to be abnormal and a free word order, as for instance, in the Russian language, where the word order may be easily changed and this change doesn’t corrupt the grammatical and logical meaning of the sentence, because such deviation doesn’t change the deep structure of the sentence; all changes take place in the surface structure. In the article, problems of a free word order in the English, German and Russian languages and the ways of their solution from the perspective of the generative grammar are highlighted.